Influence of STEM Student Worksheets to Improve Learning Outcomes and Student interest in Reaction Rate - Nia Pratiwi Siregar; Susilawati Amdayani (Universitas Negeri Medan, 2023)
This study aims to determine the effect of LKPD STEM using Problem Based Learning (PBL) model on reaction rate material. This research was conducted at SMAN 8 Medan in the 2022/2023 school year. This type of research is a quasi experiment with pretest posttest control group design. The population in this study were all XI MIPA classes at SMAN 8 Medan. The research sample was XI MIPA 4 class as an experimental class taught with STEM LKPD using Problem Based Learning (PBL) model and XI MIPA 1 class as a control taught using Problem Based Learning (PBL) model without STEM LKPD. The instruments used in this study were 20 multiple choice questions that had been tested for validity, reliability, difficulty level and differentiation, and 25 items of questionnaire statements of learning interest. The results of this study indicate that there is an effect of STEM LKPD using the Problem Based Learning (PBL) model on learning outcomes with hypothesis testing sig. 0,001 < α (0,05). In addition, there is an effect of STEM LKPD using the Problem Based Learning (PBL) model on learning interest with a hypothesis test sig. 0,000 < α (0,05).